2017
DOI: 10.1093/ecco-jcc/jjx077
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Anaemia in the First Year of Inflammatory Bowel Disease in a European Population-based Inception Cohort—An ECCO-EpiCom Study

Abstract: Overall, 42% of patients had at least one instance of anaemia during the first year following diagnosis. Most patients were assessed for anaemia regularly; however, a full anaemia work-up was frequently neglected in this community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
3
17
2
5
Order By: Relevance
“…Despite current guidelines, only 64% of the patients in this cohort received specific therapy within 3 months of the diagnosis of anaemia. Unfortunately, this is in line with other studies reflecting real‐life IBD practices . In a recent cross‐sectional study, Voegtlin et al reported that only 40% and 43% of IBS patients with anaemia in Switzerland, in private practice and university hospitals, respectively, received supplementation therapy .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Despite current guidelines, only 64% of the patients in this cohort received specific therapy within 3 months of the diagnosis of anaemia. Unfortunately, this is in line with other studies reflecting real‐life IBD practices . In a recent cross‐sectional study, Voegtlin et al reported that only 40% and 43% of IBS patients with anaemia in Switzerland, in private practice and university hospitals, respectively, received supplementation therapy .…”
Section: Discussionsupporting
confidence: 79%
“…Similar to a recent European multicentre study of patients with newly diagnosed IBD, we found that Crohn's disease patients with stricturing disease behaviour had an increased risk of anaemia as compared to patients with an inflammatory phenotype, and that extensive disease was associated with an increased risk of anaemia in ulcerative colitis . In contrast, we could not confirm that there was an increased risk in Crohn's disease patients with a colonic disease location, although the predictors of anaemia at the time of diagnosis of IBD may be different from the risk factors in the long term.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In an observational cross-sectional multicenter study including 1,313 adult Portuguese IBD patients with a median follow-up after diagnosis of 7 years, anemia was reported in 244 patients, representing a prevalence of 18.6% (95% CI 16.6−20.9) [15]. In another multicenter study including a cohort of 1,871 adult patients, the prevalence of anemia was 49% in CD patients versus 39% in UC patients during the first 12 months after diagnosis [16].…”
Section: Introductionmentioning
confidence: 95%
“…A study on the incidence of anaemia in IBD patients published by ECCO (European Crohn's and Colitis Organisation) showed that in 42% of them anaemia was found in the first year after diagnosis. It is more often found in CD patients than in UC patients [91]. e authors of numerous studies describe the relationship of hepcidin-to-iron concentration [92].…”
Section: Ironmentioning
confidence: 99%